Impact du sédiment sur les mortalités estivales de naissain d'huîtres creuses Crassostrea gigas en baie de Quiberon - Bedier, Edouard; Knoery, Joel Radford; Fleury, Pierre-gildas; Quiniou, Francoise; Langlade, Aime; Cozic, Amandine; Delesmont, Edith; Delesmont, Régis; Caisey, Xavier; Lecureuil, Laetitia (2006)
The phenomenon of summer mortalities of the Pacific cupped oyster Crassostrea gigas is observed in France since the beginning of the 90's. These mortalities are classically associated to younger stages and summer temperatures and occur during the reproduction period of the animal. The studies undertaken during the project Morest (2001-2005), showed that a number of biological and environmental risks, the interaction of them induces lethal stresses for animals in physiological weakness, exists in summer. Among these risks, that which is withstood by the oysters bred close to the sediment proved to be significant in intertidal areas. In Quiberon bay (southern Brittany, France), the breeding practices of sowing oysters in deep water is thus likely to expose oysters to these adverse conditions. The follow-up of mortality operated on the leasing grounds of the bay indicates a large variability according to the bay sectors, as well in term of absolute level of mortality as of differential between oysters bred on the ground and in open water. In the same periods, experiments confirmed that the oysters bred close to the sediment showed different physiological parameters (maturation, index of vitality) and growth compared to those kept at an elevation of 60cm from the ground. However, the levels of mortality did not reflect these differences in 2003 and 2004. The existence of reduced compounds (sulphide and ammonia) inside the sediment, and their potential flux into the suprabenthic water is required to explain this sediment effect. The results show that the solid sediment of the bay of Quiberon is a potential source of these toxic compounds, which can be found in the water column. The sulphide and ammonia concentrations measured in the water column are however below their values of acute toxicity, according to the low values of mortality recorded in 2003 and 2004. Measurements of ecotoxicity of the sediment and water column showed generally low values, lower than those found in intertidal areas. Le phénomène des ...